THE CAUSES OF WORLD WAR 3: CLASS, GEOPOLITICS AND HEGEMONY IN THE 21ST CENTURY – A RE-READING OF ARRIGHI, THROUGH MCDERMOTT, SCHUMPETER AND VEBLEN - Colatrella, Steven (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
This article investigates some of the reasons behind the events that led to a recent shift in international relations towards the global geopolitical and a renewed competition between the great powers. The aim is to point out important ideas of authors and put them to dialogue between each other. It calls attention to the possibility of an alternative political and economic bloc being built around China against a decline of US power. These points are deepened when it is identified other key features of the current system that involves the discussion about classes. The current configuration of class alliances and states involves the complex dynamics of the working classes in the Global South, the use of debt as a means of domination by the economic and financial world, as well as the new professional middle class - that give values to knowledge, technology and democracy. It is these relationships and their interface with the existing political power that permeate the revival of the global geopolitics, influencing not only current events, but also any possibility of thinking an alternative for governance and international framework - or even the failure of this and a consequent and possible new conflict worldwide.